The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/plants10071382
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spray of Alpha-Tocopherol Modulates Antioxidant Potential of Okra Fruit under Salt Stress

Abstract: As an antioxidant, alpha-tocopherol (α-Toc) protects plants from salinity-induced oxidative bursts. This study was conducted twice to determine the effect of α-Toc as a foliar spray (at 0 (no spray), 100, 200, and 300 mg L−1) to improve the yield and biochemical constituents of fresh green capsules of okra (Abelmoschus esculentus L. Moench) under salt stress (0 and 100 mM). Salt stress significantly reduced K+ and Ca2+ ion concentration and yield, whereas it increased H2O2, malondialdehyde (MDA), Na+, glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…Such an increase in sugar contents of grape berries could be related to the increased chlorophyll contents and the higher photosynthesis rate achieved through supplemental sprays of Fe, B and Zn [51]; similar findings were reported in apple and grapevines [52][53][54]. Higher sugar contents as a result of foliar sprays of micronutrients have also been reported in strawberry, pomegranate, and grapes [55][56][57].…”
Section: Discussionsupporting
confidence: 59%
“…Such an increase in sugar contents of grape berries could be related to the increased chlorophyll contents and the higher photosynthesis rate achieved through supplemental sprays of Fe, B and Zn [51]; similar findings were reported in apple and grapevines [52][53][54]. Higher sugar contents as a result of foliar sprays of micronutrients have also been reported in strawberry, pomegranate, and grapes [55][56][57].…”
Section: Discussionsupporting
confidence: 59%
“…Salinity effects could be alleviated by employing shot-gun approaches, that is, exogenous application of vitamins, nutrients, and antioxidants. One of these antioxidants is α-tocopherol, which can be exogenously applied as it is produced by plants endogenously (Naqve et al, 2021b). In this study, reduction in linseed has been alleviated by foliar spray of α-tocopherol.…”
Section: Discussionmentioning
confidence: 94%
“…Such treatments may be applied as foliar spraying or presowing seed treatment; alternatively, they may be applied to the growth medium (Hasanuzzaman et al, 2020). Tocopherol (α, β, γ, or δ) is a natural, highly liposoluble antioxidant produced by green photosynthetic organisms (Chen et al, 2016;Naseer et al, 2020), which effectively protects biological membranes from salinity-induced oxidation (Naqve et al, 2021b). α-Tocopherol restores plant growth by detoxifying singlet oxygen species and peroxides, thereby shielding photosystems, and inhibiting lipid peroxidation under saline conditions (Zandi and Schnug, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols belonging to the vitamin E group are biosynthesized by plants and regulate plant abiotic stress tolerance as an antioxidant and signaling molecule ( Ali et al, 2022 ). Naqve et al (2021) evaluated the impact alpha-tocopherol on salt-stressed okra [ Abelmoschus esculentus (L.) Moench] and observed an improvement in growth and yield via increasing the activity of antioxidants and via accumulation of Pro and GB. Moreover, the authors observed that alpha-tocopherol eased the hostile effects of salt stress by decreasing Na + uptake, MDA, and H 2 O 2 levels while boosting the uptake of K + and Ca 2+ .…”
Section: Improved Salt Tolerance By Different Priming Agentsmentioning
confidence: 99%